Self-Regulation Mediates Therapeutic Horseback Riding Social Functioning Outcomes in Youth With Autism Spectrum Disorder - Peters, B. Caitlin; Pan, Zhaoxing; Christensen, Hannah; Gabriels, Robin L. (Frontiers in Pediatrics, 2022)
Emerging evidence suggests therapeutic horseback riding improves self-regulation behaviors, social functioning, and language in youth with autism spectrum disorder (ASD). It has been theorized that interacting with horses is calming for youth with ASD, which may influence social and language outcomes. The current study is an exploratory secondary mediation analysis of a previously published randomized controlled trial of therapeutic horseback riding for youth with ASD. We hypothesized that self-regulation would mediate therapeutic horseback riding’s effect on social and language outcomes in youth with ASD. Results indicate that self-regulation mediates therapeutic horseback riding’s effect on social, but not language outcomes. This paper provides support for the hypothesis that interacting with horses may have a calming effect that serves as a platform for improving social outcomes in youth with autism.